Collabio: A Game for Annotating People within Social Networks - Bernstein, Michael; Tan, Desney; Smith, Greg; Czerwinski, Mary; Horvitz, Eric (UIST'09, 2008)
We present Collabio, a social tagging game within an online social network that encourages friends to tag one another. Collabio’s approach of incentivizing members of the social network to generate information about each other produces personalizing information about its users. We report usage log analysis, survey data, and a rating exercise demonstrating that Collabio tags are accurate and augment information that could have been scraped online.